The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.2478/10004-1254-64-2013-2328
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Damage in Turkish Coke Oven Workers Exposed to Polycyclic Aromatic Hydrocarbons: Association with CYP1A1, CYP1B1, EPHX1, GSTM1, GSTT1, and GSTP1 Gene Polymorphisms

Abstract: The aim of this study was to determine the frequencies of chromosomal aberrations (CA) and cytochalasin-blocked micronuclei (CBMN) in peripheral blood lymphocytes from Turkish coke oven workers and the influence of CYP1A1, CYP1B1, EPHX1, GSTM1, GSTT1, and GSTP1 gene polymorphisms on these biomarkers. Cytogenetic analysis showed that occupational exposure significantly increased the CA and CBMN frequencies. Gene polymorphisms, on the other hand, did not affect CA or CBMN in either exposed or control subjects. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Chromatid breaks were the most common type of chromosomal aberrations reported in their study. A similar study by Ada et al (21) aimed to determine cytogenetic damage in peripheral blood lymphocytes in Turkish coke oven workers and showed that the overall frequencies of aberrant cells without gaps were significantly higher (p < 0.001) in coke oven workers than in the control group. Chromosomal aberrations mainly consisted of breaks and chromatid gaps.…”
Section: Discussionmentioning
confidence: 92%
“…Chromatid breaks were the most common type of chromosomal aberrations reported in their study. A similar study by Ada et al (21) aimed to determine cytogenetic damage in peripheral blood lymphocytes in Turkish coke oven workers and showed that the overall frequencies of aberrant cells without gaps were significantly higher (p < 0.001) in coke oven workers than in the control group. Chromosomal aberrations mainly consisted of breaks and chromatid gaps.…”
Section: Discussionmentioning
confidence: 92%
“…No study looks at both polymorphisms in the Turkish population. Ada et al [10], while looking at only CYP1B1*4 in people working in a coke oven, Bilgin et al [18] looked at NSCLC (Non-Small Cell Lung Cancer) patients and CYP1B1*4.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies regarding the relationship of these polymorphisms with glaucoma, obesity, cardiovascular diseases, and hormone-mediated cancers [8,9]. In previous studies on the Turkish population, Ada et al [10] investigated the CYP1B1*4 polymorphism in coke oven workers with 49 people. In their study, Güler et al [11] examined CYP1B1*2 and CYP1B1*3 polymorphisms in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%